Ethnic Farmers and the “Outside” World: Mennonites in Manitoba and Nebraska, 1874-1900 - Loewen, Royden (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1990)
AbstractHistorians have suggested that two types of farmers settled on the Canadian prairie; one was the commercially oriented Anglo-Canadian farmer, the other was the European ethnic group settler bent on transplanting an “Old World” way of life on the periphery of mainstream society. These latter settlements — comprised of Ukrainians, German-Catholics, French-Canadians, Doukhobors, and Mennonites — have been described as isolated “ethnic islands in a Canadian sea”. This essay, however, argues that even the Mennonites or rural, sectarian, immigrant communities were not dependent on geographical isolation or a transplanted subsistence agriculture. It suggests that their aims were to reproduce their ethnic communities with financial resources derived from a judicious interaction with the marketplace and an adaption of agricultural practices to a new physical environment. It counters the impression that, while Anglo-Canadian farmers adapted quickly to the exigencies of their environments, ethnic farmers like the Mennonites transplanted their traditional ways without change.The essay focuses on the experience of a small but representative Mennonite immigrant group, the “Kleine Gemeinde”, who settled in both the East Reserve, Manitoba, and in Jefferson County, Nebraska in 1874. The writings of these farmers and the parallel Canadian and American public record suggest that these ethnic farmers adapted quickly to their new environments. New climates, labour conditions, and markets brought changes to their crop selections, levels of mechanization, and cultivation practices. The East Reserve farms were relatively small, mixed operations but, it is argued, that rather than suggesting a peasant existence, these facts point to rational market choices in a relatively primitive Manitoba economy. Changes that these Mennonite farmers made during their first generation in Canada reflect the development of Manitoba's economy. A comparison of East Reserve with its sister settlement in Nebraska indicates that, between 1874 and 1900, the two communities diverged significantly in their farming practices. That divergence reflected differences in the economy and physiography of Manitoba and Nebraska. More important than cultural predispositions in shaping their agriculture was the Mennonites' willingness to adapt to a new climate and cultivate a sustained relationship with the markets of the “outside world”.